Performance analysis of CIC multirate filter in cognitive radio for efficient pulse shaping in wireless domain - A. S. Kang; Er.Vishal Sharma; Prof.Renu Vig (Institute of Advanced Engineering and Science, 2019)
In this paper, the Performance Analysis of Cascade Integrator Comb Filter in context of Filter Bank Multicarrier Transmission has been presented for Cognitive radio. A benefit of the chosen technique is that, a CIC filter can be designed with a slight adjustment in parameters of interest. The entire performance of the filters designed is analyzed and evaluated by analyzing Normalized Amplitude versus Normalized Frequency plots at typical K and N values. The roll off factor plays a significant role in performance analysis of CIC filter. The results shown are a useful advance for rf design engineers working in the domain of multirate signal processing in wireless communication. To ensure the acceptable performance of Enhanced FBMC, computational complexity, and transmission burst length need to be reduced. The effect of Stop band attenuation on the edges of Magnitude and Frequency responses has been studied under constraints such as Lp, K and M during different simulation runs.